"Where There Are Stars, There Is Also Darkness": Young Icelandic Men's Experience of Prescription Drug Misuse. Issue 1 (February 2022) - Arnarsdottir, Andrea Yr; Johnsen, Arni; Thorsson, Kjartan; Sigurdardottir, Sigrun
Misuse of prescription drugs is a public health problem in many places around the world, including Iceland. It is considered most common among 18- to 25-year-olds, various risk factors and motives explain this trend. The purpose of this study was to examine young Icelandic men's experience of prescription drug misuse. Participants in this study were seven Icelandic males, 18–26 years old, mean age was 20.9. Data were collected through 14 interviews and then processed using a qualitative methodological approach based on Vancouver's school of phenomenology. The overriding theme of the study " Where there are stars, there is also darkness " refers to the common thread in participants' experiences of misuse of prescription drugs that were initially positive but quickly turned negative. Four main themes were identified: influence factors, reasons, onset, and continued drug misuse. The influencing factors were social influence, social group, lack of knowledge, and curiosity. The main reasons for the drug misuse were to suppress distress, improve capacity and efficiency, or have fun and avoid boredom. The onset of prescription drug misuse was characterized by quick fixes, misuse of one's own medication or medication from a friend/family member. Continued misuse was characterized by a vicious circle, black market, medical visits on false pretenses, and symptoms of dependence and addiction. It is necessary to highlight this public health problem that prescription drug misuse among young Icelandic males appear to be and it needs to be considered as a multifarious problem as the results indicate that its nature is truly complex.